The Effects of the Hominis Placenta Herbal acupuncture on Sleep pattern disturbance - Youn Hyoun-min; Lee Chae-woo; Kim Hong-ki (Korean Pharmacopuncture Institute, 2005)
Objective : This study has been designed and performed to identify the effects of Hominis Placenta herbal acupuncture which is usually used in reducing sleep pattern disturbances. Methods : The study subjects studied included 48 patients who were admitted in hospital located in Pusan, and they were classified into 2 groups : 25 patients in the experimental group who injected Hominis Placenta herbal acupuncture and 23 patients in the control group who were treated by acupuncture. The both group injected on GB20, GB12 and HT7 for 5 days without medicine. The sleep pattern disturbance score was measured by using 15 questions according to Korean Sleep Scale A(Oh, Jin Joo. Song, Mi Soon. Kim, Shin Mi. 1998). Results & conclusions : The sleep pattern disturbance score of the experimental group who injected Hominis Placenta herbal acupuncture was significantly lower than that of the control group. (t= 7.00 p= .00) These results provided that Hominis Placenta herbal acupuncture of GB20, GB12 and HT7 was effective for relieving sleep pattern disturbances, it is need more sample's number and more treatmentt's duration.